(3GdfaM Gdeci HeYLe TjhN Gdecis - (3CMeO GdOeTbj , CMeO Hf YKeGf GdOeTbj GdMfaj,J (B1163 (3g` s ((3eMeO Hf ESeGYjd Hf EHQGgje Gdejefi GdTgjQ HGdTfGhi s)
(3ChdgG (B:s
(3CMeO Gddg GdPi NU gPg GdCeI GdeMeOjI GdeQMheI HaVjdI YXjeI s
(3BNQgG (B:s
(3hcGf GdaQGZ ef LeYg hJCdjag Ydi jO eDdag s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B310s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B816 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B324 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs